Study on distribution and type of cardiac lesions in aborted lambs - Ramin AG; 2Hobe-Naghi R; Akbari H; Ramin (Global Journal of Food and Agribusiness Management, 2020)
Histopathological lesions in the hearts of 44 aborted lambs were investigated 1) to determine the percentage of injured hearts following abortion, 2) to determine the distribution and percentage of lesion types in the hearts of aborted lambs and 3) To clarify the probable cause of abortion on the base of histopathological cardiac lesions in Urmia, Iran. Of 44 lambs’ heart, 10 aborted lambs have had normal hearts and 34 lambs revealed one or more lesions in their hearts. The percentages of normal and injured hearts were 22.7 and 77.3%, respectively. Types of lesions in aborted lambs' heart were hyperemia, myocardial necrosis, interstitial edema, watery degeneration, haemorrhagia, hyaline degeneration and Purkinje degeneration. The distribution and percentage of lesions in the injured hearts were 20 (26.7%), 20 (26.7%), 12 (16%), 9 (12%), 8 (10.7%), 4 (5.2%) and 2 (2.6%), respectively. The percentage of lesions in the injured hearts were 58.8%, 58.8%, 35.3%, 26.5%, 23.5%, 11.8%, 5.8% and in whole lambs' heart were 45.5%, 45.5%, 27.3%, 20.5%, 18.2%, 9.2% and 4.6%, respectively. The highest distribution and percentage of lesion types in the injured hearts were hyperemia and myocardial necrosis and the lowest was Purkinje cell degeneration. In another words, up to half of the aborted lambs revealed hyperemic and myocardial necrosis in their hearts. The distribution and percentage of injured hearts appeared one, two, three and four lesions were 10 (29.4%), 18 (52.9%), 4 (11.8%) and 2 (5.9%), respectively. According to the cardiac lesion types, the majority of aborted lambs have had primarily of secondary cardiac lesions in that foot and mouth disease is the primary one and vitamin E&Se deficiency could be the second one. It is concluded that types of cardiac lesions would be useful in diagnosis, control and treatment of diseases if local history diseases support them.